Constructions of migrant victims of labor exploitation in Nordic court cases - Schoultz, Isabel (International review of victimology, 2024)
The aim of this article is to explore how courts produce certain representations of victims of labor exploitation in the Nordic context based on court judgments from Denmark, Finland, Norway, and Sweden. To achieve this, we analyze and compare criminal court judgments focused on the exploitation of migrant workers by asking: How are ‘victims’ of labor exploitation represented in Nordic court judgments? What is left unproblematic and silenced? In each country, we have identified criminal court cases that have legally examined aspects of the exploitation of migrant workers, in total, 91 court judgments. Drawing on Bacchi’s ‘What’s the problem represented to be?’ (WPR) approach, we can show that the representations of victims apparent in the court judgments involve a legal construction of vulnerability that is reserved for the most marginalized migrant workers. The narrow representation silences the broader socio-economic context in which migrant workers exist. Our results also indicate that the threshold for being defined as a victim of labor exploitation is lower in some of the Nordic countries and higher in others. Thus, while there is a normative consensus that the exploitation of migrant workers should be prosecuted, in practice, the court judgments reflect substantial differences in the legal interpretations applied across the Nordic countries.